2019
DOI: 10.3389/fenvs.2019.00184
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse- and Field-Measured Plant-Soil Feedbacks Are Not Correlated

Abstract: Plant-soil feedbacks (PSFs) have become a commonly invoked mechanism of plant coexistence and abundance. Yet, most PSF experiments have been performed in greenhouse conditions. To test whether or not greenhouse-measured PSF values are of similar magnitude and positively correlated with field-measured PSFs, we compared PSF values from five different studies that measured PSF values in both greenhouse and field conditions. For 36 plant species, greenhouse-measured PSF values were larger than and not positively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 48 publications
2
59
1
Order By: Relevance
“…It is important to note that only 9% of these studies were conducted in the field, suggesting that we have little inference for the strength or direction that environmental variation will demonstrate when interacting with PSF to affect plant growth. The few interactive effects shown here both support and contradict studies showing that PSF can differ between greenhouse and field experiments in different environments (Putten et al, 2016;Schittko et al, 2016;Florianová and Münzbergová, 2018;Heinze and Joshi, 2018;Kivlin et al, 2018) demonstrating how little is understood about the function of PSF in nature (Forero et al, 2019).…”
Section: Experiments Location and Soil Conditioning Source Affect Thesupporting
confidence: 53%
See 2 more Smart Citations
“…It is important to note that only 9% of these studies were conducted in the field, suggesting that we have little inference for the strength or direction that environmental variation will demonstrate when interacting with PSF to affect plant growth. The few interactive effects shown here both support and contradict studies showing that PSF can differ between greenhouse and field experiments in different environments (Putten et al, 2016;Schittko et al, 2016;Florianová and Münzbergová, 2018;Heinze and Joshi, 2018;Kivlin et al, 2018) demonstrating how little is understood about the function of PSF in nature (Forero et al, 2019).…”
Section: Experiments Location and Soil Conditioning Source Affect Thesupporting
confidence: 53%
“…An experiment by Schittko et al (2016) for example, found that the majority of plant species in an experiment exhibited positive PSF under controlled greenhouse conditions, but did not exhibit any significant PSF under natural field conditions. A meta-analysis of the PSF literature seems to corroborate this observation-experiments conducted in the greenhouse often produce larger effect sizes in PSF than those conducted in the field Forero et al, 2019). This broad pattern likely suggests that the true importance of PSF on the landscape is different than what is measured in greenhouse studies.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, we suggest that DNA-sequencing techniques of soil micro-organisms will be needed to advance our understanding of the role of soil biota in wind mediated PSF–root-morphology interactions. As wind is an environmental factor typically excluded under greenhouse conditions ( Heinze et al 2016 ; Forero et al 2019 ) our results provide a potential explanation for reported differences in PSFs between greenhouse and field. Overall, wind-induced changes in PSFs were not very strong in the current short-term study.…”
Section: Discussionmentioning
confidence: 65%
“…the outcome of PSFs). Furthermore, we aimed to test these effects under realistic wind conditions and not with electric fans in a greenhouse where natural wind is mostly excluded ( Heinze et al 2016 ; Forero et al 2019 ). Therefore, we performed a field experiment with four grassland plant species and investigated above- and belowground biomass, root morphological traits of fine roots and PSFs at two different wind levels to answer the following questions:…”
Section: Introductionmentioning
confidence: 99%